MOTIVASI MEMBAGIKAN KONTEN TANAMAN HIAS DI SOCIAL NETWORKING SITES - Cyntia Claudia; Joseph Edwin (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
Covid-19 is a pandemic that acts as a catalyst for drastic lifestyle change for people around the world. Measures to limit the spread of the disease causes majority of Indonesians to work and study at home. This spurs the growth of social networking sites (SNS) usage. Stay-at-home order also gives rise to the popularity of ornamental plant collecting. The combination of the two activities is evident in the phenomena of posting contents about ornamental plant collection in SNS. According to uses gratification perspective, new communication technologies and the subsequent activities they facilitate function to satisfy the needs of the audiences. This research aims to explore the motivation typologies that are related to posting ornamental plant contents on SNS. Qualitative data was collected from 5 informants based on grounded theory procedures. Through semi-structured interview, three types of typologies were found. The first is classic typology that includes entertainment, pastime, identity management, social interaction and knowledge sharing. Second is expanded typology; social influencing and economic motivation. The third is emergent typology that includes sharing positivity. This article serves as a preliminary research that delves into communication phenomena during the Covid-19 pandemic. It is recommended that future research validate the typologies found by performing quantitative studies.